Harmonisasi Budaya Masyarakat Lokal dan Keturunan Arab di Kelurahan Nyamplungan dalam Perspektif Teori Praktik Sosial Pierre Bourdieu - Rohmah, Lila Faqih Azi Nor; Asih, Dwi Suti; Nadiyya, Fatikha Aulia Alinta; Ilmi, M. Wahlul (The Sociology of Islam, 2023)
The research was conducted on ethnic Javanese and Arab descent in the Nyamplungan, Pabean Cantian District, Surabaya City, East Java, using field research. The objectives of the research conducted were: To find out the harmonization that exists between the two local ethnic Javanese and Arabs, to look for patterns of harmonization that are intertwined through social capital for the process of cultural harmonization. This research uses a method with a case study approach, with observation techniques, interviews with each clan, and a literature study of journals related to research on cultural harmonization. By using Pierre Bourdieu's theory of social practice it is hoped that it can show harmony between cultural harmonization that occurs in local Javanese and Arab communities. The results of the research show that the social practices that Bourdieu said that they already have a habitus and social capital from generation to generation to continue to build close cultural harmonization. Second, local and Arab communities are open to each other so that it is said that there are minimal conflicts that occur and they tend to live side by side. Third, they have rules to maintain the existence of culture so that its existence is maintained. Keywords: Cultural Harmonization, Social Practices, Arab Ethnicity, Pierre Bourdieu